2020
DOI: 10.1101/2020.03.05.976233
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploring the evolution and adaptive role of mosaic aneuploidy in a clonalLeishmania donovanipopulation using high throughput single cell genome sequencing

Abstract: 14Maintenance of stable ploidy over continuous mitotic events is a paradigm for most higher 15 eukaryotes. Defects in chromosome segregation and/or replication can lead to aneuploidy, a 16 condition often considered deleterious. However, in Leishmania, a Protozoan parasite, 17aneuploidy is a constitutive feature, where variations of somies represent a mechanism of gene 18 expression adaptation, possibly impacting phenotypes. Strikingly, clonal Leishmania 19 populations display cell-to-cell somy variation, a ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…Interestingly, large-scale research involving a large number of samples and wide geographic range has revealed that genetic diversity is significantly higher than that previously reported ( Bussotti et al., 2018 ; Zackay et al., 2018 ; Franssen et al., 2020 ; Imamura et al., 2020 ; Patino et al., 2020 ; Salloum et al., 2020 ; Zheng et al., 2020 ; Patino et al., 2021 ; Schwabl et al., 2021 ). Recently, single-cell sequencing has demonstrated the presence of several distinct karyotypes within the same Leishmania clone ( Imamura et al., 2020 ; Negreira et al., 2020 ), and multiple-genotype infections have been demonstrated to occur even within the same host and tissue ( Cupolillo et al., 2020 ).…”
Section: Importance Of Genetic Diversity and Genome Plasticity Of Leishmaniamentioning
confidence: 99%
“…Interestingly, large-scale research involving a large number of samples and wide geographic range has revealed that genetic diversity is significantly higher than that previously reported ( Bussotti et al., 2018 ; Zackay et al., 2018 ; Franssen et al., 2020 ; Imamura et al., 2020 ; Patino et al., 2020 ; Salloum et al., 2020 ; Zheng et al., 2020 ; Patino et al., 2021 ; Schwabl et al., 2021 ). Recently, single-cell sequencing has demonstrated the presence of several distinct karyotypes within the same Leishmania clone ( Imamura et al., 2020 ; Negreira et al., 2020 ), and multiple-genotype infections have been demonstrated to occur even within the same host and tissue ( Cupolillo et al., 2020 ).…”
Section: Importance Of Genetic Diversity and Genome Plasticity Of Leishmaniamentioning
confidence: 99%
“…Leishmania spp. have remarkably plastic genomes, with genomic alterations such as aneuploidy (Mannaert et al, 2012;Lachaud et al, 2014), and CNVs (Rogers et al, 2011;Bussotti et al, 2018), which seems to be widespread phenomena among the species (Rogers et al, 2011;Lachaud et al, 2014;Negreira et al, 2020). Interspersed throughout the genome of Leishmania spp.…”
Section: The Contribution Of Dsbs To Genomic Changes In Leishmania Sppmentioning
confidence: 99%
“…We are however currently revisiting concepts and moving from genome-wide approaches in parasite populations (or clones) to single-cell-based strategies to better understand the plasticity of Leishmania parasites that harbor mosaic aneuploidy—a feature that has impairments in the way the parasite will respond or not to a given drug. Using a single-cell genomic sequencing method, Negreira et al (2020) identified 128 different karyotypes in 1560 L. donovani promastigotes [ 136 ]. They highlight the fact that some karyotypes presented pre-existing adaptations to antimony-based drugs, supporting a hypothesis raised even before this hint [ 137 , 138 ].…”
Section: Genome-wide Approaches In Target and Resistance (Resistommentioning
confidence: 99%